AN ANALYSIS OF CHARACTER EDUCATION OF ENGLISH TEXTBOOK “WHEN ENGLISH RINGS A BELL” FOR EIGHTH GRADE OF JUNIOR HIGH SCHOOL - Nurhaeda Gailea; Syafrizal Syafrizal; Yusti Fargianti; Shela Mutiara Perdana (Universitas Islam Nahdlatul Ulama Jepara, 2019)
The current study is aimed at investigating embedded characters that can be found in the English textbook entitled When English Rings a Bell for Eighth Grade of Junior High School. More specifically, this study is to analyze whether picture and utterance reflect the eighteen character building values. This study was qualitative approach using content analysis. The data used in this study were in the forms of utterances and pictures in the textbook. The primary instrument of the research was the researcher and the questionnaire was also employed as the second instrument. Some steps were undertaken during the data collection: reading utterances and regarding pictures carefully, understanding specific parts related to the research focus intensively, selecting the utterances and pictures related to the research questions, making a description of the data accompanied by a coding process and inserting the data into the table, analyzing the data with eighteen character, and distributing the questionnaire to the rater in order to validate the analysis of each data. The results related to the occurrence of characters, all 18 characters described by Kemendiknas were found in the pictures and utterances of an English textbook entitled When English Rings a Bell for eighth grade of junior high school. Friendliness/ communication character was the most dominant character found in the pictures and utterances with 38 data. It implied that the authors wanted to raise the students’ friendliness/ communication.